Prototipe Smartclass: Sistem Pengaturan Suhu AC Otomatis Menggunakan Mikrokontroler Dan Sensor DHT-22 Di Universitas Dirgantara Marsekal Suryadarma - Reza Para Adilla Ramadhany; Tateng Sukendar (JURNAL TEKNOLOGI INDUSTRI, 2026)
Thermal comfort in lecture rooms is an important factor in supporting the effectiveness of learning in higher education. Manual operation of Air Conditioners that is still applied in various educational institutions shows limitations in responding to changes in environmental conditions dynamically. This study aims to develop a prototype of an automatic Air Conditioner temperature control system based on Wemos D1 Mini microcontroller and DHT-22 sensor integrated with the Home Assistant platform to support the Smartclass concept at Universitas Dirgantara Marsekal Suryadarma. An experimental method with an Internet of Things prototype development approach was applied through stages of literature study, hardware and software design, implementation, and system testing. The test results show that the DHT-22 sensor is able to read temperature with a very good level of accuracy, producing an average error of 0.93% for indoor conditions and 0.98% for outdoor. The Infrared transmitter module functions optimally at an effective distance of up to 7 meters with a 100% success rate in sending control commands. The system is proven to be able to maintain room temperature stability according to the setpoint determined automatically without requiring manual intervention. Integration with Home Assistant enables real-time remote monitoring and control, creating a comfortable learning environment while increasing energy efficiency in modern classrooms.